I paesaggi nelle campagne di Roma - Alessandra, Cazzola (Scuole di dottorato, 2005)
This book presents the results of research carried out by the author over the three years of the PhD in Landscape Design at Florence University. The first part of the work focuses on the theoretical and methodological aspects of the study of the agricultural landscape and the description of its component elements, the process of its formation and the evolution of its structure. The second part represents a practical application of these observations, with an original elaboration of the relations that have given rise to the various types of agricultural landscape into which the Roman countryside can be broken down. In short, the scope of the research is to set into relation a cognitive model of the agrarian landscape with a specific territorial framework rich in emblematic landscape situations, setting itself the objective of testing the feasibility of the application of individual interpretations and proposals, and of reappraising the role of the agrarian landscape within the current process of environmental and landscape redevelopment.